Why electoral integrity matters - Norris, Pippa (New York : Cambridge University Press, 2014)
"This book is the first in a planned trilogy by Pippa Norris on chal lenges of electoral integrity to be published by Cambridge University P ress. Unfortunately too often elections around the globe are deeply fla wed or even fail. Why does this matter? It is widely suspected that suc h contests will undermine confidence in elected authorities, damage vot ing turnout, trigger protests, exacerbate conflict, and occasionally le ad to regime change. Well-run elections, by themselves, are insufficien t for successful transitions to democracy. But flawed, or even failed, contests are thought to wreck fragile progress. Is there good evidence for these claims? Under what circumstances do failed elections undermin e legitimacy? With a global perspective, using new sources of data for mass and elite evidence, this book provides fresh insights into these m ajor issues"--
Machine generated contents note: Part I. Introduction: 1. Theories w hy electoral integrity matters; 2. Concepts; 3. Evidence; Part II. The Problem of Flawed Elections: 4. International concern about electoral i ntegrity; 5. Public perceptions of electoral integrity; Part III. The C onsequences of Electoral Integrity: 6. For legitimacy; 7. For political behavior; 8. For conflict and security; 9. For regimes; Part IV. Concl usions: 10. Conclusions: strengthening electoral integrity.
Includes bibliographical references and index.
Keywords: Elections -- Management; Elections -- Corrupt practices; Election monitoring; Legitimacy of governments; Representative government and representation